High-performance interfacial modification type anti-stripping agent and preparation method thereof
Patent Information
- Application Number
- CN202610920125.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-24
- Publication Date
- 2026-10-23
AI Technical Summary
[0007]本发明有益效果为:通过对有机硅烷原料实施酸性环境下的分段引水受限水解,并依据第一状态信号和第二状态信号对活化进程进行窗口锁定,再将活化硅醇子体系在限定停留时段内导入油相接收子体系,随后以分段方式引入多胺类化合物与含磷羟基有机物形成的极性子体系,使活化硅醇锚定位点、多胺极性位点和含磷羟基配位位点在橡胶油连续相中完成协同组装,从而获得分布更稳定的界面活性结构,实现对集料表面的有效锚定、对沥青相的良好相容、对湿热作用下界面结构的持续保持,并使所得抗剥落剂具备良好的黏附保持性能、抗水损害性能、热稳定性能和服役耐久性能。
Smart Images

Figure CN122958097A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of road engineering material additives technology, and in particular to a high-performance interface-modified anti-stripping agent and its preparation method. Background Technology
[0002] Asphalt mixture anti-stripping agent technology has gradually evolved from using single amines to improve adhesion to a multi-functional component approach that synergistically regulates interfacial structure. In existing technologies, polyamine compounds, phosphorus-containing hydroxyl organic compounds, fatty acid components, and organosilanes are all used to enhance the interfacial interaction between asphalt and aggregates. Among these, organosilanes act as interfacial anchoring agents, phosphorus-containing hydroxyl organic compounds coordinate with the aggregate surface, and polyamine compounds enhance polarity. These related systems have become an important development direction for asphalt interfacial modification.
[0003] The main problem with existing related technologies is that organosilanes are prone to insufficient activation or premature self-condensation during the preparation process, which makes it difficult for them to complete orderly assembly with subsequently introduced polyamine compounds and phosphorus-containing hydroxyl organic compounds under suitable interfacial conditions. This leads to the dispersion of interfacial active sites and the attenuation of anchoring effect, making it difficult to simultaneously maintain the adhesion, water damage resistance and thermal stability of asphalt mixtures. Summary of the Invention
[0004] In view of this, this application provides a high-performance interface-modified anti-stripping agent and its preparation method.
[0005] According to one aspect of this disclosure, a high-performance interface-modified anti-stripping agent is provided, comprising, by weight: 40 parts rubber oil; 15-50 parts polyamine compound; 3-20 parts phosphorus-containing hydroxyl organic compound; 5-35 parts unsaturated fatty acid; 0.1-2 parts sodium benzylaminobenzenesulfonate; and 0.1-2 parts organosilane.
[0006] According to another aspect of this disclosure, a method for preparing a high-performance interface-modified anti-stripping agent is also provided, comprising: adding an organosilane raw material to an alcohol dispersion medium, subjecting the organosilane raw material to restricted hydrolysis in a local interface region by segmented water introduction under an acidic activation environment, and obtaining an organosilane activated subsystem under the condition of isolating free polyamines; simultaneously collecting a first state signal characterizing the degree of hydrolysis progression and a second state signal characterizing the initiation trend of self-condensation or aggregation on the organosilane activated subsystem; stopping segmented water introduction when the first state signal enters the target activation region and the second state signal is still before the aggregation initiation region, thereby obtaining a window. A locked activated silanol subsystem is obtained; rubber oil, unsaturated fatty acids, and sodium benzylaminobenzenesulfonate are mixed to obtain an oil phase receiving subsystem, and the activated silanol subsystem is introduced into the oil phase receiving subsystem within a limited residence period after locking the activated silanol subsystem to obtain a pre-anchored oil phase; a polar subsystem formed by polyamine compounds and phosphorus-containing hydroxyl organic compounds is introduced into the pre-anchored oil phase in a segmented manner, and the first direct contact period between the free polyamine and the activated silanol subsystem is controlled within a limited time interval to obtain an interfacial synergistic assembly system; the interfacial synergistic assembly system is subjected to staged devolatilization and curing treatment to obtain a high-performance interfacial modified anti-stripping agent.
[0007] The beneficial effects of this invention are as follows: by performing segmented water-restricted hydrolysis on organosilane raw materials under acidic conditions, and locking the activation process window according to the first and second state signals, the activated silanol subsystem is introduced into the oil phase receiving subsystem within a limited residence period. Subsequently, a polar subsystem formed by polyamine compounds and phosphorus-containing hydroxyl organic compounds is introduced in a segmented manner, so that the activated silanol anchoring points, polyamine polar sites, and phosphorus-containing hydroxyl coordination sites can be synergistically assembled in the continuous phase of rubber oil, thereby obtaining a more stable interfacial active structure. This achieves effective anchoring of the aggregate surface, good compatibility with the asphalt phase, and continuous maintenance of the interfacial structure under humid heat. The resulting anti-stripping agent also has good adhesion retention performance, water damage resistance, thermal stability, and service durability. Attached Figure Description
[0008] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the following description of the embodiments will be briefly introduced. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0009] Figure 1 This is a flowchart illustrating the preparation method of a high-performance interface-modified anti-stripping agent.
[0010] Figure 2 This is a comparison chart of process test results.
[0011] Figure 3 This is a comparison chart of the results of formulation stability and interfacial adhesion tests.
[0012] Figure 4 This is a comparison chart of the service performance test results of asphalt mixtures. Detailed Implementation
[0013] To make the objectives, technical solutions, and advantages of the embodiments of this disclosure clearer, the technical solutions of the embodiments of this disclosure will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this disclosure. All other embodiments obtained by those skilled in the art based on the described embodiments of this disclosure without creative effort are within the scope of protection of this disclosure.
[0014] The present invention aims to construct a high-performance interface-modified anti-stripping agent, which, by weight, comprises: 40 parts of rubber oil; 15-50 parts of polyamine compound; 3-20 parts of phosphorus-containing hydroxyl organic compound; 5-35 parts of unsaturated fatty acid; 0.1-2 parts of sodium benzylaminobenzenesulfonate; and 0.1-2 parts of organosilane.
[0015] In some embodiments of this application, the rubber oil is an aromatic oil with an aromatic hydrocarbon content of 85%; the polyamine compound is triethylenetetramine; the phosphorus-containing hydroxyl organic compound is a monoalkyl ether phosphate triethanolamine salt or sodium dodecyl phosphate; and the unsaturated fatty acid is a compound of tetraenoic acid and pentaenoic acid.
[0016] The aminosilanes and long-chain organosilanes described in this application are all liquid organosilane raw materials with hydrolyzable organosilicon groups. Specifically, the aminosilanes are selected from those possessing both amino groups and hydrolyzable groups, capable of forming a continuous hydrolysis process in both ethanol dispersion media and acidic activation environments. The long-chain organosilanes are selected from those possessing both hydrophobic long-chain structures and hydrolyzable groups, capable of maintaining dispersion compatibility after the activated silanol subsystem is introduced into the oil phase receiving subsystem. When aminosilanes and long-chain organosilanes are compounded according to the mass ratio described in this application, they should be able to form recordable first and second state signal changes during the segmented water introduction process, and should not experience premature precipitation, significant stratification, or rapid aggregation when introduced into the oil phase receiving subsystem after window locking. The polyamine compounds, phosphorus-containing hydroxyl organic compounds, and unsaturated fatty acids are respectively triethylenetetramine, monoalkyl ether phosphate triethanolamine salt, or sodium dodecyl phosphate, as described in the embodiments of this application, and a compound of tetraenoic acid and pentaenoic acid.
[0017] In some embodiments of this application, the application of high-performance interface-modified anti-stripping agents in asphalt mixtures is described.
[0018] This application also provides a method for preparing a high-performance interface-modified anti-stripping agent, such as... Figure 1 The process includes: adding an organosilane raw material to an alcohol dispersion medium; subjecting the organosilane raw material to restricted hydrolysis in a local interface region using a segmented water-injection method under an acidic activation environment; and obtaining an activated organosilane subsystem under conditions of isolating free polyamines; simultaneously collecting a first state signal characterizing the degree of hydrolysis progression and a second state signal characterizing the initiation trend of self-condensation or aggregation on the activated organosilane subsystem; stopping the segmented water-injection when the first state signal enters the target activation region and the second state signal is still before the aggregation initiation region, thus obtaining a window-locked activated silanol subsystem; and adding rubber oil, etc. Saturated fatty acids and sodium benzylaminobenzenesulfonate are mixed to obtain an oil phase receiving subsystem. The activated silanol subsystem is then introduced into the oil phase receiving subsystem within a limited residence period after locking in the activated silanol subsystem, resulting in a pre-anchored oil phase. A polar subsystem formed by polyamine compounds and phosphorus-containing hydroxyl organic compounds is introduced into the pre-anchored oil phase in a segmented manner, controlling the initial direct contact period between the free polyamine and the activated silanol subsystem to be within a limited time interval, thus obtaining an interfacial synergistic assembly system. The interfacial synergistic assembly system undergoes staged devolatilization and curing treatments to obtain a high-performance interfacial modified anti-stripping agent.
[0019] Preferably, the organosilane raw material is a mixture of aminosilane and long-chain organosilane, wherein the aminosilane accounts for 35% to 55% of the total mass of the organosilane raw material, and the long-chain organosilane accounts for 55% to 65% of the total mass of the organosilane raw material.
[0020] Preferably, the alcohol dispersion medium is ethanol; the acidic activation environment is provided by a phosphorus-containing hydroxyl organic compound, or by a combination of a phosphorus-containing hydroxyl organic compound and an acidic regulating medium.
[0021] The acidic activation environment described in this application is used to maintain the organosilane feedstock in a controlled hydrolysis state during the staged water introduction process. In a preferred embodiment, the acidic activation environment is provided solely by an acidic conditioning medium, or jointly by the acidic conditioning medium and the phosphorus-containing hydroxyl organic compound used in subsequent formulations. When the phosphorus-containing hydroxyl organic compound is not directly added at the beginning of activation, the acidic conditions required for activation are provided first by the acidic conditioning medium. After the activated silanol subsystem completes window locking, the phosphorus-containing hydroxyl organic compound participates in subsequent interfacial co-assembly. Thus, the stability of the initial restricted hydrolysis process is maintained, while the premature intervention of free polyamines is avoided to prevent disturbance to the activated silanol state.
[0022] Preferably, the first state signal is selected from at least one of the release rate of volatile low molecular weight alcohols, the rate of change in conductivity, and the rate of change in acid value, and the second state signal is selected from at least one of the turbidity growth rate, the particle size growth rate, and the viscosity growth rate.
[0023] In a preferred embodiment of this application, the first state signal is the rate of change of conductivity, and the second state signal is the rate of change of turbidity. The rates of change of conductivity and turbidity are used as the direct basis for window locking, residence time determination, and sequence control. The release rate of volatile low-molecular-weight alcohols, the rate of change of acid value, the particle size growth rate, and the viscosity growth rate are used only as optional state signals to verify their correspondence with the aforementioned direct basis. Only when these optional state signals, under the same raw material system, the same total amount of water, the same activation temperature, and the same sampling interval, give a consistent interval determination result with the rate of change of conductivity or the rate of change of turbidity, can they be used as equivalent substitute signals. For optional state signals that cannot form a consistent interval determination result, the determination results of the rate of change of conductivity and the rate of change of turbidity shall prevail.
[0024] Preferably, the segmented water diversion method involves introducing water phase in small amounts multiple times, while maintaining a shear-dispersion state between adjacent water diversions; From the moment the activated silanol subsystem is locked until it is introduced into the oil phase receiving subsystem, the residence time of the activated silanol subsystem in the original activation environment does not exceed the time limit.
[0025] Preferably, the oil phase receiving subsystem does not contain polyamine compounds or phosphorus-containing hydroxyl organic compounds; the polar subsystem is introduced into the pre-anchored oil phase in a pulsed addition manner or a metered segmented addition manner.
[0026] Preferably, the staged devolatilization includes a low-temperature alcohol removal stage and a high-temperature aging stage, wherein the processing temperature of the low-temperature alcohol removal stage is 60–85°C and the processing temperature of the high-temperature aging stage is 95–110°C.
[0027] To further illustrate the impact of the process control methods of the present invention, which utilize restricted hydrolysis, dual-state signal monitoring, window locking, time-limited transition to the oil phase, and segmented introduction of polar subsystems, on the performance of anti-stripping agents, process tests, formulation stability and interfacial adhesion tests, and asphalt mixture service performance tests were conducted on the samples prepared in the examples and comparative examples. The process tests were used to characterize the window-locking state and transition state of the activated silanol subsystem, the formulation stability and interfacial adhesion tests were used to characterize the structural stability and interfacial interaction ability of the anti-stripping agent, and the asphalt mixture service performance tests were used to characterize the anti-stripping agent's resistance to water damage, thermal stability, and service durability under actual application conditions.
[0028] In the process testing, the organosilane raw material was added to an ethanol dispersion medium and an acidic conditioning medium. Water was introduced in stages under constant temperature and stirring conditions, with timing starting from the first introduction of the aqueous phase. During activation, conductivity data was continuously collected using an online conductivity probe, and turbidity data was continuously collected using an online turbidity probe. The ratio of the conductivity difference between two adjacent sampling points to the sampling time interval was used as the first state signal value, and the ratio of the turbidity difference between two adjacent sampling points to the sampling time interval was used as the second state signal value. The time point at which water introduction was stopped was recorded as the window locking time. The first and second state signal values corresponding to the window locking time were... The first state signal value and the second state signal value at the time of window locking are recorded respectively. The time from the time of window locking until the activated silanol subsystem is completely introduced into the oil phase receiving subsystem is recorded as the dwell time after window locking. The time from the time of window locking until the first polar subsystem containing polyamine compounds comes into direct contact with the pre-anchored oil phase is recorded as the first contact time of free polyamine. The time of window locking, the first state signal value at the time of window locking, the second state signal value at the time of window locking, the dwell time after window locking, and the first contact time of free polyamine are recorded as process test results in Table 1, which is used to compare the process differences between the examples and the comparative examples in the activation stage and the transition stage.
[0029] In the preparation process of this application, the target activation interval, aggregation initiation interval, limited residence time, and time-limited interval are all determined based on continuous trial production records under the same raw material system. Under the condition of maintaining consistent organosilane composition, ethanol dosage, acidic adjustment medium addition, total water volume, and activation temperature, the first and second state signals during the segmented water introduction process are continuously recorded. The period during which the first state signal continuously rises and the second state signal does not show a continuous sudden increase is taken as the target activation interval suitable for sequence transition. The starting position where the second state signal changes from a slow change to a continuous increase is taken as the starting point of the aggregation initiation interval. The residence time range during which the activated silanol subsystem is introduced into the oil phase receiving subsystem without abnormal viscosity, significant turbidity deepening, or increased stratification of subsequent samples after water introduction is stopped is taken as the limited residence time. The contact time range during which the first contact point of the free polyamine is maintained within the above-mentioned limited residence time and the resulting sample still has stable interfacial adhesion results is taken as the time-limited interval.
[0030] In the formulation stability and interfacial adhesion tests, the initial viscosity of the prepared anti-stripping agent samples was measured under a constant temperature of 25℃. The samples were then sealed and placed in a 50℃ environment for 7 days. After returning to room temperature, the viscosity after storage was measured, and the viscosity change rate after storage was calculated based on the viscosity values before and after storage. Simultaneously, the sample stratification was observed and the stratification height was measured. Additionally, modified asphalt was prepared by adding each anti-stripping agent to the same base asphalt at the same dosage. Aggregates from the same source and within the same particle size range were coated with the modified asphalt, and the coated aggregates were then soaked in room temperature water. The adhesion grade after water treatment was assessed based on the residual asphalt area on the aggregate surface after immersion in room temperature water. The adhesion retention rate after hot water treatment was calculated based on the ratio of the residual coating area to the initial coating area on the aggregate surface after hot water treatment. The viscosity, viscosity change rate after storage, delamination height, adhesion grade after water treatment, and adhesion retention rate after hot water treatment were recorded as the results of the formulation stability and interfacial adhesion test in Table 2, which were used to compare the storage changes and coating retention under water treatment conditions of the anti-stripping agents obtained in the examples and comparative examples.
[0031] In the service performance testing of asphalt mixtures, anti-stripping agents were added to the same base asphalt at the same dosage, and asphalt mixture specimens were prepared under the same aggregate gradation, the same asphalt-aggregate ratio, and the same molding conditions. One group of specimens was subjected to water immersion treatment, and the stability value after treatment was measured. Simultaneously, the stability value of the un-immersed specimens was also measured. The ratio of the stability value after water immersion treatment to the stability value before water immersion was used as the water immersion stability retention index. Another group of specimens underwent freeze-thaw cycle treatment, and the splitting tensile strength after treatment was measured. Simultaneously, the splitting tensile strength of the un-freeze-thawed specimens was also measured. The ratio of the splitting tensile strength after freeze-thaw cycle treatment to the splitting tensile strength before freeze-thaw cycle treatment was used as the freeze-thaw strength retention index. A third group of specimens underwent long-term water immersion treatment, and the splitting tensile strength after treatment was measured. Simultaneously, the splitting tensile strength of the un-immersed reference specimen was also measured. The ratio of the splitting tensile strength after long-term immersion to the baseline splitting tensile strength before immersion was used as the interface retention index after long-term immersion. Loose asphalt mixtures were subjected to heat storage treatment, and specimens were formed, with the corresponding water stability retention index measured. Simultaneously, the water stability retention index of loose asphalt mixture specimens without heat storage treatment was measured. The ratio of the water stability retention index after heat storage treatment to the water stability retention index before heat storage was used as the retention index after heat storage. The water stability retention index, freeze-thaw strength retention index, interface retention index after long-term immersion, and retention index after heat storage were recorded as the asphalt mixture service performance test results in Table 3, used to compare the performance retention of the examples and comparative examples after water treatment, freeze-thaw treatment, and heat storage treatment.
[0032] All performance tests in this application were compared under the same raw material source and sample preparation conditions. In the formulation stability and interfacial adhesion tests, each sample was measured in parallel using the same sampling amount, the same settling conditions, and the same aggregate source, and the average of the parallel results was recorded. In the asphalt mixture service performance test, each sample was prepared using the same base asphalt, the same aggregate gradation, the same asphalt-aggregate ratio, and the same molding regime, and was compared under the same immersion, freeze-thaw, long-term immersion, and heat storage conditions to ensure that the differences between different samples originated from differences in the anti-stripping agent preparation process, rather than differences in sample preparation conditions.
[0033] Example 1: Based on the weight of the finished product, take 40 parts rubber oil, 28 parts triethylenetetramine, 10 parts triethanolamine monoalkyl ether phosphate salt, 12 parts tetraenoic acid, 8 parts pentaenoic acid, 0.8 parts sodium benzylaminobenzenesulfonate, and 1.2 parts organosilane, of which 0.48 parts are aminosilane and 0.72 parts are long-chain organosilane. Add the organosilane to 6 parts ethanol, then add 0.20 parts glacial acetic acid, and stir at 28°C. Add 0.48 parts aqueous phase in four equal portions, maintaining shear dispersion between adjacent water infusions. After the third water infusion, continue shearing until the window lock time is 8.4 min, and the first state signal value at window lock is 0.37 ms. · When the window is locked, the second state signal value is 1.88 NTU. The water introduction was stopped, resulting in a window-locked activated silanol subsystem. Separately, rubber oil, unsaturated fatty acids, and sodium benzylaminobenzenesulfonate were mixed to form an oil-phase receiving subsystem. Within 3.1 minutes after window locking, the activated silanol subsystem was introduced into the oil-phase receiving subsystem to obtain a pre-anchored oil phase. Triethylenetetramine and monoalkyl ether phosphate triethanolamine salt were premixed to form a polar subsystem, which was added to the pre-anchored oil phase in three portions at 20%, 40%, and 40% of the total amount. The first contact time of the free polyamine was 4.3 minutes. After the addition was complete, the mixture was devolatilized at 75°C for 30 minutes, then heated to 102°C for 55 minutes to obtain the anti-stripping agent. The obtained anti-stripping agent had a viscosity of 478 mPa·s, a viscosity change rate of 4.8% after storage, a delamination height of 0.4 mm, an adhesion grade of 4.8 after water treatment, and an adhesion retention rate of 93.7% after hot water treatment. The corresponding asphalt mixture exhibited a water immersion stability retention index of 92.1%, a freeze-thaw strength retention index of 89.4%, an interface retention index of 88.2% after long-term water immersion, and a retention index of 95.1% after hot storage.
[0034] Example 2: The composition of this example is the same as that of Example 1, except that the window locking position is moved forward. Organosilane, ethanol, and glacial acetic acid are mixed as in Example 1, and 0.48 parts of aqueous phase are added in four equal portions. After the second water introduction is completed, shearing continues, with the window locking time at 6.5 minutes. The first state signal value at window locking is 0.30 ms. · When the window is locked, the second state signal value is 1.29 NTU. The water infusion was stopped, resulting in a window-locked activated silanol subsystem. Subsequent processes were the same as in Example 1, with a dwell time of 3.0 min after window locking and an initial contact time of 4.1 min for the free polyamine. The resulting anti-stripping agent had a viscosity of 461 mPa·s, a viscosity change rate of 4.5% after storage, a delamination height of 0.6 mm, an adhesion grade of 4.5 after water treatment, and an adhesion retention rate of 90.9% after hot water treatment. The corresponding asphalt mixture exhibited a water immersion stability retention of 89.7%, a freeze-thaw strength retention of 87.1%, an interface retention of 85.8% after long-term water immersion, and a retention rate of 93.3% after thermal storage.
[0035] Example 3: The composition of this example is the same as that of Example 1, except that the window locking position is moved backward. Organosilane, ethanol, and glacial acetic acid are mixed as in Example 1, and 0.48 parts of aqueous phase are added in four equal portions. After the fourth water introduction is completed, shearing continues, and the window locking time is 10.2 minutes. The first state signal value at window locking is 0.41 ms. · When the window is locked, the second state signal value is 2.53 NTU. The water infusion was stopped, resulting in a window-locked activated silanol subsystem. Subsequent processes were the same as in Example 1, with a dwell time of 3.2 min after window locking and an initial contact time of 4.4 min for the free polyamine. The resulting anti-stripping agent had a viscosity of 492 mPa·s, a viscosity change rate of 6.4% after storage, a delamination height of 0.9 mm, an adhesion grade of 4.3 after water treatment, and an adhesion retention rate of 88.8% after hot water treatment. The corresponding asphalt mixture exhibited a water immersion stability retention of 88.4%, a freeze-thaw strength retention of 86.8%, an interface retention of 83.9% after long-term water immersion, and a retention rate of 92.2% after thermal storage.
[0036] Example 4 follows the same process steps as Example 1, except that the internal ratio of the organosilane is adjusted to 0.42 parts aminosilane and 0.78 parts long-chain organosilane. The organosilane is added to 6 parts ethanol, followed by 0.20 parts glacial acetic acid, and stirred at 28°C. 0.48 parts aqueous phase is added in four equal portions. After the third water introduction, shearing continues, with the window locking time at 8.8 minutes. The first state signal value at window locking is 0.35 ms. · When the window is locked, the second state signal value is 1.67 NTU. The water introduction was stopped, resulting in a window-locked activated silanol subsystem. Subsequently, the oil phase receiving subsystem was introduced as in Example 1, and the polar subsystem was added in three separate additions. The dwell time after window locking was 2.9 min, and the first contact time of the free polyamine was 4.0 min. The resulting anti-stripping agent had a viscosity of 451 mPa·s, a viscosity change rate of 3.8% after storage, a delamination height of 0.3 mm, an adhesion grade of 4.6 after water treatment, and an adhesion retention rate of 91.8% after hot water treatment. The corresponding asphalt mixture exhibited a water immersion stability retention index of 90.8%, a freeze-thaw strength retention index of 87.9%, an interface retention index of 86.6% after long-term water immersion, and a retention index of 95.6% after thermal storage.
[0037] Example 5 follows the same process steps as Example 1, except that the internal ratio of the organosilane is adjusted to 0.54 parts aminosilane and 0.66 parts long-chain organosilane. The organosilane is added to 6 parts ethanol, followed by 0.20 parts glacial acetic acid, and stirred at 28°C. 0.48 parts aqueous phase is added in four equal portions. After the third water introduction, shearing continues, with the window locking time at 8.1 min. The first state signal value at window locking is 0.41 ms. · When the window is locked, the second state signal value is 2.14 NTU. The water introduction was stopped, resulting in a window-locked activated silanol subsystem. Subsequently, the oil phase receiving subsystem was introduced as in Example 1, and the polar subsystem was added in three separate additions. The dwell time after window locking was 3.0 min, and the first contact time of the free polyamine was 4.2 min. The resulting anti-stripping agent had a viscosity of 507 mPa·s, a viscosity change rate of 5.5% after storage, a delamination height of 0.5 mm, an adhesion grade of 4.9 after water treatment, and an adhesion retention rate of 93.1% after hot water treatment. The corresponding asphalt mixture exhibited a water immersion stability retention index of 91.4%, a freeze-thaw strength retention index of 88.7%, an interface retention index of 87.3% after long-term water immersion, and a retention index of 94.3% after thermal storage.
[0038] Example 6 follows the same process as Example 1, except that the phosphorus-containing hydroxyl organic compound is replaced with sodium dodecyl phosphate instead of monoalkyl ether phosphate triethanolamine salt. By weight of the finished product, 40 parts rubber oil, 28 parts triethylenetetramine, 10 parts sodium dodecyl phosphate, 12 parts tetraenoic acid, 8 parts pentaenoic acid, 0.8 parts sodium benzylaminobenzenesulfonate, and 1.2 parts organosilane are taken, including 0.48 parts aminosilane and 0.72 parts long-chain organosilane. The organosilane is added to 6 parts ethanol, followed by 0.22 parts glacial acetic acid, and stirred at 28°C. 0.48 parts aqueous phase is added in four equal portions. After the third water introduction, shearing continues, with the window locking time at 9.0 min. The first state signal value at window locking is 0.34 ms. · When the window is locked, the second state signal value is 1.82 NTU. The water introduction was stopped, resulting in a window-locked activated silanol subsystem. Subsequently, the oil phase receiving subsystem was introduced as in Example 1, and the polar subsystem was added in three separate additions. The residence time after window locking was 3.1 min, and the first contact time of the free polyamine was 4.3 min. The resulting anti-stripping agent had a viscosity of 469 mPa·s, a viscosity change rate of 5.3% after storage, a delamination height of 0.7 mm, an adhesion grade of 4.4 after water treatment, and an adhesion retention rate of 90.5% after hot water treatment. The corresponding asphalt mixture exhibited a water immersion stability retention index of 89.5%, a freeze-thaw strength retention index of 86.9%, an interface retention index of 85.1% after long-term water immersion, and a retention index of 93.1% after thermal storage.
[0039] Comparative Example 1: The components were prepared according to the composition of Example 1. No restricted hydrolysis of organosilanes was performed, no monitoring of the first and second state signals was conducted, no window locking was performed, and the dwell time after window locking and the initial contact time of the free polyamine were not controlled. Rubber oil, unsaturated fatty acids, sodium benzylaminobenzenesulfonate, triethylenetetramine, monoalkyl ether phosphate triethanolamine salt, and organosilane were added to the same container at once and stirred at 60°C for 90 min. Subsequently, the mixture was devolatilized at 75°C for 30 min, and then heated to 102°C for 55 min to obtain the comparative sample. No window locking process was recorded in this group. The obtained sample had a viscosity of 603 mPa·s, a viscosity change rate of 14.9% after storage, a segregation height of 3.4 mm, an adhesion grade of 2.6 after water treatment, and an adhesion retention rate of 73.5% after hot water treatment. The corresponding asphalt mixture had a water immersion stability retention index of 75.8%, a freeze-thaw strength retention index of 70.9%, an interface retention index of 67.4% after long-term water immersion, and a retention index of 84.7% after hot storage.
[0040] Comparative Example 2: The components were prepared according to the composition of Example 1. Organosilane was added to 6 parts ethanol, followed by 0.20 parts glacial acetic acid, and stirred at 28°C. 0.48 parts aqueous phase was added in four equal portions. After complete water introduction, the mixture remained in the original activation environment before being introduced into the oil phase receiving subsystem. The recorded values when all water introduction was stopped were: time 9.7 min, first state signal value 0.45 ms. · The second state signal value is 3.72 NTU. The residence time after stopping water introduction was 10.4 min, and the initial contact time of free polyamines was 11.2 min. Subsequently, the polar subsystem was added in three portions, and the samples were devolatilized at 75℃ for 30 min and matured at 102℃ for 55 min to obtain comparative samples. The obtained samples had a viscosity of 586 mPa·s, a viscosity change rate of 16.1% after storage, a segregation height of 3.0 mm, an adhesion grade of 3.1 after water treatment, and an adhesion retention rate of 78.2% after hot water treatment. The corresponding asphalt mixture exhibited a water immersion stability retention index of 79.4%, a freeze-thaw strength retention index of 74.6%, an interface retention index of 71.8% after long-term water immersion, and a retention index of 85.9% after hot storage.
[0041] Comparative Example 3: The components were prepared according to the composition of Example 1. The organosilane restricted hydrolysis step was performed as in Example 1; after the third water introduction, shearing continued, with the window locking time at 8.4 min, and the first state signal value at window locking was 0.37 ms. · When the window is locked, the second state signal value is 1.88 NTU. The water introduction was stopped, resulting in a window-locked activated silanol subsystem. The difference was that this activated silanol subsystem was not introduced into the oil-phase receiving subsystem within a limited time period, but rather remained in the original activation environment for 14.6 min before being introduced into the oil-phase receiving subsystem. The initial contact time of the free polyamine was 15.7 min. Subsequently, the polar subsystem was added in three portions, and the samples were devolatilized at 75℃ for 30 min and matured at 102℃ for 55 min to obtain comparative samples. The obtained samples had a viscosity of 545 mPa·s, a viscosity change rate of 12.8% after storage, a stratification height of 2.7 mm, an adhesion grade of 3.3 after water treatment, and an adhesion retention rate of 80.6% after hot water treatment. The corresponding asphalt mixture exhibited a water immersion stability retention index of 81.0%, a freeze-thaw strength retention index of 77.5%, an interface retention index of 73.9% after long-term water immersion, and a retention index of 88.3% after thermal storage.
[0042] Comparative Example 4: Components were prepared according to the composition of Example 1. The organosilane restricted hydrolysis and window locking steps were performed as in Example 1; after the third water introduction, shearing continued, with the window locking time at 8.5 min, and the first state signal value at window locking was 0.37 ms. · When the window is locked, the second state signal value is 1.90 NTU. The water introduction was stopped, resulting in a window-locked activated silanol subsystem. The difference lies in that rubber oil, unsaturated fatty acids, sodium benzylaminobenzenesulfonate, triethylenetetramine, and monoalkyl ether phosphate triethanolamine salt were pre-mixed in the same reactor to form a receiving system containing a polar subsystem. After the window was locked, the activated silanol subsystem was directly introduced into the receiving system within 3.0 min, with the first contact time of the free polyamine being 3.0 min. Subsequently, it was devolatilized at 75℃ for 30 min, and then cured at 102℃ for 55 min to obtain a comparative sample. The obtained sample had a viscosity of 541 mPa·s, a viscosity change rate of 11.6% after storage, a segregation height of 2.0 mm, an adhesion grade of 2.1 after water treatment, and an adhesion retention rate of 74.8% after hot water treatment. The corresponding asphalt mixture had a water immersion stability retention index of 77.6%, a freeze-thaw strength retention index of 72.4%, an interface retention index of 69.2% after long-term water immersion, and a retention index of 86.5% after hot storage.
[0043] Comparative Example 5: The components were prepared according to the composition of Example 1. The steps of restricted hydrolysis of organosilanes, window locking, and introduction of the activated silanol subsystem into the oil phase receiving subsystem were all performed as in Example 1; after the third water introduction, shearing continued, with the window locking time at 8.4 min, and the first state signal value at window locking was 0.37 ms. · When the window is locked, the second state signal value is 1.87 NTU. The dwell time after window locking was 3.1 min. The difference lies in that the polar subsystem formed by triethylenetetramine and monoalkyl ether phosphate triethanolamine salt was added entirely to the pre-anchored oil phase at once, without segmented addition, resulting in the first contact time of the free polyamine at 3.8 min. Subsequently, it was devolatilized at 75℃ for 30 min, then heated to 102℃ for 55 min to obtain the comparative sample. The obtained sample had a viscosity of 514 mPa·s, a viscosity change rate of 9.2% after storage, a segregation height of 1.6 mm, an adhesion grade of 3.4 after water treatment, and an adhesion retention rate of 82.5% after hot water treatment; the corresponding asphalt mixture's water immersion stability retention index was 83.6%, its strength retention index after freeze-thaw cycles was 79.3%, its interface retention index after long-term water immersion was 75.7%, and its retention index after hot storage was 89.1%.
[0044] Table 1. Results of Programmatic Testing
[0045] To more intuitively illustrate the process differences between the various embodiments and comparative examples in the activation and transition stages, the window locking time, dwell time after window locking, first contact time of free polyamine, and first and second state signal values at window locking are further plotted in Table 1. Figure 2 .Depend on Figure 2 It can be seen more clearly that there are significant differences among different samples in terms of window locking position, dwell time and contact time, thus providing a process basis for subsequent comparison of formulation status and application results.
[0046] Table 2 Results of formulation stability and interfacial adhesion tests
[0047] To more intuitively illustrate the differences in storage conditions and interfacial adhesion between the anti-stripping agents obtained in each embodiment and comparative example, the viscosity, viscosity change rate after storage, delamination height, adhesion grade after water treatment, and adhesion retention rate after hot water treatment in Table 2 are further plotted as follows: Figure 3 .Depend on Figure 3 It can be seen that the samples are not completely identical in terms of formulation stability parameters and interfacial adhesion parameters, indicating that different process conditions have different effects on storage state and interfacial retention results.
[0048] Table 3. Service performance test results of asphalt mixtures
[0049] To more intuitively illustrate the performance retention of the asphalt mixtures in each embodiment and comparative example under different service conditions, the water immersion stability retention index, freeze-thaw strength retention index, long-term water immersion interface retention index, and heat storage retention index in Table 3 are further plotted as follows: Figure 4 .Depend on Figure 4 It can be seen that the service performance of the mixtures in the example group is generally higher than that in the comparative group, indicating that the anti-stripping agent prepared according to the process route of the present invention can maintain a good application effect at the mixture scale.
[0050] As shown in Table 1, Examples 1-6 all recorded the window locking time, the first state signal value at window locking, the second state signal value at window locking, the dwell time after window locking, and the first contact time of the free polyamine. This indicates that each example was prepared according to the process route of restricted hydrolysis, window locking, and time-limited transposition. Among them, Examples 2 and 3 correspond to earlier and later window locking, respectively; Examples 4 and 5 correspond to the adjustment of the bissilane ratio; and Example 6 corresponds to the replacement of phosphorus-containing hydroxyl organic matter. Comparative Examples 2, 3, 4, and 5 correspond to continued dwell, delayed transposition, early contact, and one-time addition, respectively. This shows that there are clear process differences between the samples in the activation and transposition stages.
[0051] As shown in Table 2, the anti-stripping agents obtained in Examples 1-6 exhibited generally lower viscosity change rates and stratification heights after storage, and higher adhesion grades after water treatment and adhesion retention rates after hot water treatment, all superior to Comparative Examples 1-5. Example 1 showed relatively balanced overall results, Example 4 demonstrated superior formulation stability, and Example 5 demonstrated superior interfacial adhesion, indicating that variations in the bissilane ratio have different effects on different performance indicators. Comparative Example 1 performed poorly overall, Comparative Example 2 showed unfavorable storage changes, and Comparative Example 4 showed unfavorable interfacial adhesion, indicating that without control according to the process route of this invention, the storage state and interfacial retention results of the obtained anti-stripping agents would both decline.
[0052] As shown in Table 3, the water immersion stability retention index, freeze-thaw strength retention index, long-term water immersion interface retention index, and heat storage retention index of the asphalt mixtures corresponding to Examples 1-6 are generally higher than those of Comparative Examples 1-5, indicating that the anti-stripping agent obtained by the process route of this invention can maintain good application results at the mixture scale. Among them, Example 1 has the best overall results, Example 4 is more outstanding in terms of heat storage retention, and Example 5 is more outstanding in terms of water immersion and freeze-thaw related indicators. Comparative Example 1 has the lowest overall results, Comparative Example 3 is higher than some comparative examples, but still lower than the Example group, and Comparative Example 4 is low in terms of long-term water immersion interface retention index, indicating that continued immersion, premature contact, or changes in the addition method will have an adverse effect on the service results of the mixture.
[0053] The above description is only a specific embodiment of this disclosure, but the protection scope of this disclosure is not limited thereto. The protection scope of this disclosure should be determined by the protection scope of the claims.
Claims
1. A method for preparing a high-performance interface-modified anti-stripping agent, characterized in that, include: Organosilane raw materials are added to an alcohol dispersion medium, and under acidic activation conditions, the organosilane raw materials are subjected to restricted hydrolysis in local interface regions by a segmented water-guiding method, and an organosilane activated subsystem is obtained under the condition of isolating free polyamines. Simultaneously collect a first state signal characterizing the degree of hydrolysis progression and a second state signal characterizing the initiation trend of self-condensation or aggregation on the organosilane activation subsystem. Stop segmented water diversion when the first state signal enters the target activation interval and the second state signal is still before the aggregation initiation interval to obtain the window-locked activated silanol subsystem. Rubber oil, unsaturated fatty acids and sodium benzylaminobenzenesulfonate are mixed to obtain an oil phase receiving subsystem. The activated silanol subsystem is then introduced into the oil phase receiving subsystem within a limited residence period after locking the activated silanol subsystem to obtain a pre-anchored oil phase. A polar subsystem formed by polyamine compounds and phosphorus-containing hydroxyl organic compounds is introduced into the pre-anchored oil phase in a segmented manner, and the first direct contact interaction period between the free polyamine and the activated silanol subsystem is controlled within a time limit to obtain an interfacial synergistic assembly system. The interface co-assembly system is subjected to staged devolatilization and curing treatment to obtain a high-performance interface-modified anti-stripping agent.
2. The preparation method according to claim 1, characterized in that, The organosilane raw material is a mixture of aminosilane and long-chain organosilane, wherein the aminosilane accounts for 35% to 55% of the total mass of the organosilane raw material, and the long-chain organosilane accounts for 55% to 65% of the total mass of the organosilane raw material.
3. The preparation method according to claim 1, characterized in that, The alcohol dispersion medium is ethanol; The acidic activation environment is provided by phosphorus-containing hydroxyl organic compounds, or by a combination of phosphorus-containing hydroxyl organic compounds and an acidic regulating medium.
4. The preparation method according to claim 1, characterized in that, The first state signal is selected from at least one of the release rate of volatile low molecular weight alcohol, the rate of change of conductivity, and the rate of change of acid value, and the second state signal is selected from at least one of the turbidity growth rate, the particle size growth rate, and the viscosity growth rate.
5. The preparation method according to claim 1, characterized in that, The segmented water diversion method involves introducing water phase in small amounts multiple times, while maintaining a shear-dispersion state between adjacent water diversions; From the moment the activated silanol subsystem is locked until it is introduced into the oil phase receiving subsystem, the residence time of the activated silanol subsystem in the original activation environment does not exceed the time limit.
6. The preparation method according to claim 1, characterized in that, The oil phase receiver system does not contain polyamine compounds or phosphorus-containing hydroxyl organic compounds; The polar subsystem is introduced into the pre-anchored oil phase via a pulsed addition method or a metered, segmented addition method.
7. The preparation method according to claim 1, characterized in that, The phased devolatilization includes a low-temperature alcohol removal dispersing medium removal stage and a high-temperature aging stage. The processing temperature of the low-temperature alcohol removal dispersing medium removal stage is 60-85℃, and the processing temperature of the high-temperature aging stage is 95-110℃.
8. A high-performance interface-modified anti-stripping agent, characterized in that, Prepared by the preparation method according to any one of claims 1 to 7, comprising, by weight: 40 parts of rubber oil; Polyamine compounds, 15-50 parts; 3-20 parts of phosphorus-containing hydroxyl organic compounds; 5-35 parts of unsaturated fatty acids; Sodium benzylaminobenzenesulfonate 0.1–2 parts; 0.1 to 2 parts of organosilane.
9. The high-performance interface-modified anti-stripping agent according to claim 8, characterized in that, The rubber oil is an aromatic oil with an aromatic hydrocarbon content of 85%; The polyamine compound is triethylenetetramine; The phosphorus-containing hydroxyl organic compound is a monoalkyl ether phosphate triethanolamine salt or sodium dodecyl phosphate; The unsaturated fatty acid is a compound of tetraenoic acid and pentaenoic acid.
10. The application of the high-performance interface-modified anti-stripping agent according to claim 8 or 9 in asphalt mixtures.